The Effect Of Audit Committee, Internal Auditor And Audit Quality On Firm Value - Octaviani, Santi (Publisher Cv. Inara, 2023)
This study aims to determine the effect of internal auditor on company value, audit quality on company value, internal audit on company value with the audit committee as a moderating variable and audit quality on company value with the audit committee as a moderating variable in consumer goods sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research was conducted using quantitative methods with a casualty approach. This study totaled 54 companies and was sampled as many as 12 companies using the purposive sampling method. Data analysis using SPSS version 25. Based on the results of partial and Moderated Regression Analysis (MRA), it can be concluded that: 1) Internal Auditor does not have a significant effect on Company Value, 2) Audit Quality has a significant effect on Company Value, 3) The Audit Committee cannot moderate the influence of Internal Auditor on Company Value, 4) The Audit Committee can moderate the effect of Audit Quality on Company Value.